Detection of non-cardiac fetal abnormalities on ultrasound at 11–14 weeks: systematic review and meta-analysis - Karim, JN; Di Mascio, D; Roberts, N; Papageorghiou, AT (Wiley, 2024)
Objectives To assess the diagnostic accuracy of two-dimensional ultrasound at 11–14 weeks' gestation as a screening test for individual fetal anomalies and to identify factors impacting on screening performance.